THE EFFECT OF CYBERLOAFING BEHAVIOR, LOCUS OF CONTROL, AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE WITH ISLAMIC WORK ETHIC AS MODERATOR (Case Study at PT Kebon Agung Trangkil Pati Sugar Factory) - Amelia Novita Sari; Saifudin Saifudin (Imara: JURNAL RISET EKONOMI ISLAM, 2022)
The purpose of this study was to determine the effect of cyberloafing behavior, locus of control, and work discipline on performance with an Islamic work ethic as a moderator. This type of research is a quantitative study with a population of PT Kebon Agung Trangkil Pati employees. The sampling technique in this study used purposive sampling, which collected 84 respondents. From the results of data analysis, it shows that: (1) Cyberloafing behavior has no significant positive effect on employee performance (2) Locus of control has a positive and significant effect on employee performance (3) Work discipline has a positive and significant effect on employee performance (4) Islamic work ethic can moderate the influence of cyberloafing behavior on employee performance (5) Islamic work ethic can moderate the effect of locus of control on employee performance (6) Islamic work ethic can moderate the effect of work discipline on employee performance at PT Kebon Agung Trangkil Pati